Teachers and Parents Collaboration in Literacy and The Student Character Learning - Martati, Badruli; Haryanti, Tining (Journal of Nonformal Education, 2023)
An intelligent nation can be developed through character education by cultivating the main character values. Several schools have implemented it that there has been a change in patterns due to the Covid-19 pandemic. The purpose of this research: the first to find a model of civilizing the main character values through literacy in Muhammadiyah Elementary school/MI. the second, knowing the impact of cultivating the values of the main character through literacy in Muhammadiyah Elementary school/MI students. Phenomenological approach to explore based on the concept point of view of Muhammadiyah Elementary school/MI students in Surabaya as research informants. Using survey methods, field observations, interviews, documentation, and triangulation. Data processing with software of ATLAS.ti. The results showed that the main character values have been applied. It was reflected in the daily behaviour of students in worshiping without being ordered, loving and maintaining the good name of Indonesia. Wearing batik clothes as a form of nationalism, studying well, doing assignments on time independently. Caring for friends by sharing, throwing garbage in its place, Not bullying, not taking the rights of others as anti-corruption behaviour and a form of love for the truth